Analysis of Industry Needs for Indonesian Vocational Education Services Using the EduQual-IPA Method - Gofur, Muhamad; Hasibuan, Sawarni (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
The Indonesia's Open Unemployment Rate (TPT) is 5.45% or reached 7.99 million people as of February 2023. Therefore, government support and continuous improvement of the training-based curriculum system are needed. Link and match between Indonesian vocational education and the industrial world needs to be built so that Indonesian vocational graduates are significantly absorbed by the industry. The Indonesian vocational education curriculum needs to be developed together by involving the Business and Industrial World with a vision of implementation based on needs. The purpose of this research is to find out the educational service variables in Indonesian vocational learning needed by the industrial world. So that it can be used as a reference for vocational education in improving service quality. The results of research using EDUQUAL-IPA integration show that there are four priority variables that are the focus of improvement, namely; learning outcomes 1 (ability to use the latest technology), learning outcomes 2 (practical orientation in education), Physical facilities 8 (effective classroom management) and academics 4 (channeling the interests and talents of graduates).